SOCIETY INFORMATION NEEDS IN BORDER AND UNDERDEVELOPED AREAS IN NORTH SULAWESI AND GORONTALO - KEBUTUHAN INFORMASI MASYARAKAT DI DAERAH PERBATASAN DAN TERTINGGAL DI PROVINSI SULAWESI UTARA DAN GORONTALO - Christopel Herman Kanter (BPSDMP Kominfo Manado, 2016)
AbstractUUD 1945 put the significance of the information in section 28F, that the state is present in the fulfillment of the rights of citizens to obtain and use information. It was stated in the Target RPJMN 2015-2019, namely